The lack of UME6 sustain 2- deoxy-D-glucose toxicity under inositol limitation condition in Saccharomyces cerevisiae - Ravi, Chidambaram; Nachiappan, Vasanthi (International Journal of Scientific Research in Biological Sciences, 2019)
The glucose analogues 2-DG exposure affects glycolytic enzymes. Glucose-6 P is the precursor for the synthesis of myo-inositol metabolism, 2-DG exposer reduced myo-inositol level. In the current study, we found UME6 deletion depict resistance to the 2-DG toxicity. The UME6 deletion increased the INO1 β-galactosidase activity even the exposer of 2-DG in (0.025% and 0.05%) under I− condition compared to WT cells. The sever growth impairment was observed in 0.025% concentration of 2-DG, and also severally affects the INO1 transcription in WT cells under inositol deprivation. The 0.05% concentration highly toxic no growth was observed under inositol limitation, which led to abolish the INO1 transcription in WT cells. The UME6 transcription factor negatively regulates INO1 transcription this could be the reason for the resistance ume6∆ strain of 2-DG toxicity with I− condition. We conclude that the ume6∆ resistant with the exposure of 2-DG under inositol limitation condition in Saccharomyces cerevisiae